Integrating pollen and sedimentary DNA refines reconstructions of vegetation change through human settlement: a case study from Lake Waihau, Aotearoa New Zealand - Xun Li; Georgia Thomson-Laing; Marcus J. Vandergoes; Jamie D. Howarth; Susanna A. Wood (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Late Holocene climate variability and lake productivity change inferred from the remote alpine catchment of Lake Bright, New Zealand - Julian Eschenroeder; Christopher M. Moy; Sebastian Naeher; Marcus J. Vandergoes; Oliver Rach; Dirk Sachse; Rik Tjallingii; Jamie D. Howarth; Adelaine Moody; Xun Li; Claire Shepherd; Elizabeth Kennedy; et al. (Quaternary Science Reviews, 2026)

Proterozoic highly siderophile element enrichment of the Kaapvaal cratonic Archean mantle - Nadine P. Cooper; D. Graham Pearson; Andreas Auer; Tristan Bongartz; Yannick Bussweiler; Mario Fischer-Gödde; Max Hellers; Geoffrey Howarth; Andrew J. Locock; Ambre Luguet; Carsten Münker; Thomas Stachel; et al. (Chemical Geology, 2026)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Earthquake-triggered submarine canyon flushing transfers young terrestrial and marine organic carbon into the deep sea - Katherine L Maier; Catherine E Ginnane; Sebastian Naeher; Jocelyn C Turnbull; Scott D Nodder; Jamie Howarth; Sarah J Bury; Robert G Hilton; Jess IT Hillman (Earth and Planetary Science Letters, 2025)

Integrated onshore–offshore paleoseismic records show multiple slip styles on the plate interface, central Hikurangi subduction margin, Aotearoa New Zealand - Charlotte O. Pizer; Jamie D. Howarth; Kate J. Clark; Alan R. Orpin; Stephanie E. Tickle; Lorna J. Strachan; Philip Barnes; Sian Camp; Monique Mckeown; Emily Twort (Quaternary Science Reviews, 2024)

Lacustrine mass movements in active tectonic settings: Lake tsunami sources in New Zealand's South Island - Katie E. Hughes; Sean J. Fitzsimons; Jamie D. Howarth (Geomorphology, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Sedimentary ancient DNA reveals the impact of anthropogenic land use disturbance and ecological shifts on fish community structure in small lowland lake - Georgia Thomson-Laing; Jamie D. Howarth; Javier Atalah; Marcus J. Vandergoes; Xun Li; John K. Pearman; Sean Fitzsimons; Chris Moy; Adelaine Moody; Claire Shepherd; Nicholas McKay; Susanna A. Wood (Science of The Total Environment, 2024)

A paleoecological investigation of recent cyanobacterial blooms and their drivers in two contrasting lakes - Caitlin Wheeler; John K. Pearman; Jamie D. Howarth; Marcus J. Vandergoes; Katherine Holt; Steven A. Trewick; Xun Li; Lucy Thompson; Georgia Thomson-Laing; Mailys Picard; Chris Moy; Nicholas P. Mckay; et al. (Harmful Algae, 2024)

A taxonomy-free diatom eDNA-based technique for assessing lake trophic level using lake sediments - Rose Gregersen; John K. Pearman; Javier Atalah; Sean Waters; Marcus J. Vandergoes; Jamie D. Howarth; Georgia Thomson-Laing; Lucy Thompson; Susanna A. Wood (Journal of Environmental Management, 2023)

Characterizing carotenoids in cyanobacterial cultures – Opportunities and implications for paleolimnological studies - Jonathan Puddick; Sebastian Naeher; John K Pearman; Carrie D Page; Donato Romanazzi; Lena A Schallenberg; Jamie D Howarth; Marcus J Vandergoes; Susanna A Wood (Harmful Algae, 2023)

It's all in the mud - The use of sediment geochemistry to estimate contemporary water quality in lakes - Sean Waters; Javier Atalah; Lucy Thompson; Georgia Thomson-Laing; John K. Pearman; Jonathan Puddick; Jamie D. Howarth; Lizette Reyes; Marcus J. Vandergoes; Susanna A. Wood (Applied Geochemistry, 2023)

An integrated proximal-distal radiocarbon dating approach provides improved age constraints for a key Holocene tephra isochron - Charlotte O. Pizer; Jamie D. Howarth; Kate J. Clark; Colin J.N. Wilson; Stephanie E. Tickle; Jenni L. Hopkins; Jenny A. Dahl (Quaternary Science Reviews, 2023)

Paleo-diatom records reveal ecological change not detected using traditional measures of lake eutrophication - Rose Gregersen; Jamie D. Howarth; Javier Atalah; John K. Pearman; Sean Waters; Xun Li; Marcus J. Vandergoes; Susanna A. Wood (Science of The Total Environment, 2023)

Deterministic processes drive national‐scale patterns in lake surface sediment bacteria and eukaryotic assemblage composition - John K. Pearman; Janet Adamson; Georgia Thomson‐Laing; Lucy Thompson; Sean Waters; Marcus J. Vandergoes; Jamie D. Howarth; Susanna A. Wood (Limnology and Oceanography, 2023)
Biological communities within lake surface sediments play a vital role in biogeochemical cycling and ecosystem services. Knowledge on abundance‐occupancy patterns and assembly processes across large spatial scales and over multiple environmental gradients is limited, yet essential to aid in protection and restoration. In the present study, surface sediment samples were collected from 296 lakes across a wide spatial scale and covering multiple interacting environmental gradients including size, depth, altitude, and trophic state. A suite of physicochemical parameters were used to characterize the environmental conditions and bacterial and eukaryotic assemblages were determined using 16S and 18S rRNA metabarcoding. The majority (~ 55%) of amplicon sequence variants were only found in a single lake with eukaryotes having a more restricted distribution than bacteria. Deterministic processes were inferred to be dominant for both bacteria (78%) and eukaryotes (51%), with variable selection being especially important for bacteria (49%). Variation partitioning indicated that land use in the catchment, which is strongly related to trophic state, was the most important environmental factor in explaining the assemblage composition. This nationwide study across broad gradients provides new insights into the ecology of bacteria and eukaryotes in lake surface sediments and a platform to better understand the effects of multiple environmental stressors on lake sediment assemblages.

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Multidisciplinary Scientific Cruise to the Rio Grande Rise - Luigi Jovane; James R. Hein; Isobel A. Yeo; Mariana Benites; Natascha M. Bergo; Paulo V. F. Corrêa; Daniel M. Couto; Ayrton D. Guimarães; Sarah A. Howarth; Henrique R. Miguel; Kira L. Mizell; Denise S. Moura; et al. (Frontiers in Marine Science, 2019)

Effects of ecosystem protection on scallop populations within a community-led temperate marine reserve - Leigh M. Howarth; Callum M. Roberts; Julie P. Hawkins; Daniel J. Steadman; Bryce D. Beukers-Stewart (Marine Biology, 2015)

Candidate locus analysis of the TERT–CLPTM1L cancer risk region on chromosome 5p15 identifies multiple independent variants associated with endometrial cancer risk - Luis G. Carvajal-Carmona; Tracy A. O’Mara; Jodie N. Painter; Felicity A. Lose; Joe Dennis; Kyriaki Michailidou; Jonathan P. Tyrer; Shahana Ahmed; Kaltin Ferguson; Catherine S. Healey; Karen Pooley; Jonathan Beesley; et al. (Human Genetics, 2015)

Genetic Diversity and Population Structure Among Oat Cultivars and Landraces - G. Montilla-Bascón; J. Sánchez-Martín; N. Rispail; D. Rubiales; L. Mur; T. Langdon; I. Griffiths; C. Howarth; E. Prats (Plant Molecular Biology Reporter, 2013)

Effects of streptozotocin-induced diabetes on connexin43 mRNA and protein expression in ventricular muscle - F. C. Howarth; N. J. Chandler; S. Kharche; J. O. Tellez; I. D. Greener; T. T. Yamanushi; R. Billeter; M. R. Boyett; H. Zhang; H. Dobrzynski (Molecular and Cellular Biochemistry, 2008)

Development of genic-microsatellite markers for sorghum staygreen QTL using a comparative genomic approach with rice - G. Srinivas; K. Satish; S. Murali Mohan; R. Nagaraja Reddy; R. Madhusudhana; D. Balakrishna; B. Venkatesh Bhat; C. J. Howarth; N. Seetharama (Theoretical and Applied Genetics, 2008)

Reconciling Carbon-cycle Concepts, Terminology, and Methods - F. S. Chapin; G. M. Woodwell; J. T. Randerson; E. B. Rastetter; G. M. Lovett; D. D. Baldocchi; D. A. Clark; M. E. Harmon; D. S. Schimel; R. Valentini; C. Wirth; J. D. Aber; et al. (Ecosystems, 2006)

Regional distribution of metallothionein and zinc in the mouse gut - C. D. Tran; R. N. Butler; J. C. Philcox; A. M. Rofe; G. S. Howarth; P. Coyle (Biological Trace Element Research, 1998)